KAJIAN YURIDIS KASUS POLITIK UANG PADA PILKADA ANALISIS: PENANGANAN SENTRA PENEGAKAN HUKUM TERPADU (GAKKUMDU) TERHADAP PELANGGARAN PIDANA PEMILU - Yarsina, Nova; Rahmad, Rahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This research aims to determine the handling of money politics crimes during regional head elections, carried out by regional head candidate participants, voters and campaign teams in regional head elections. The empirical legal research used is a documentation study method, then the data obtained is analyzed descriptively qualitatively so as to reveal the expected results and conclusions. The results of this research show that: the handling of violations of criminal acts of money politics by the Integrated Law Enforcement Center (Gakkumdu) is carried out with the provisions of the flow of handling election violations based on Perbawaslu No. 8 of 2020, there are factors that influence the Integrated Law Enforcement Center in handling criminal acts of money politics at the General Election Supervisory Body in general, there are 3 main problems, namely legal substance, legal structure, legal culture, it is hoped that the handling will be carried out by the Law Enforcement Center Integrated (Gakkumdu) Against Criminal Election Violations, especially Criminal Election Violations in Money Politics Cases, will increase public confidence in the organizers of the upcoming election. Keywords: Crime, money politics, regional head elections.